Jobs for Shared Prosperity : Time for Action in the Middle East and North Africa - Gatti, Roberta; Morgandi, Matteo; Grun, Rebekka; Brodmann, Stefanie; Angel-Urdinola, Diego; Moreno, Juan Manuel; Marotta, Daniela; Schiffbauer, Marc; Mata Lorenzo, Elizabeth (Washington, DC: World Bank, 2013)
In the aftermath of the Arab Spring, when thousands of young women and men fought for the opportunity to realize their aspirations and potential, the question of jobs continues to be crucial in the Middle East and North Africa region. This report uses jobs as a lens to weave together the complex dynamics of employment creation, skills supply, and the institutional environment of labor markets. Consistent with the framework of the 2013 World Development Report on jobs, of which this report is the regional companion, this work goes beyond the traditional links between jobs, productivity, and living standards to include an understanding of how jobs matter for individual dignity and expectations—an aspect that was clearly central to the Arab Spring. Just as important, this report complements the economic perspective with an analysis of political economy equilibrium, with a view to identifying mechanisms that would trigger a reform process. As such, the report has three objectives: First, it seeks to provide an in-depth characterization of the dynamics of labor markets in the Middle East and North Africa and to analyze the barriers to the creation of more and better jobs. It does so by taking a cross-sectoral approach and identifying the distortions and incentives that the many actors—firms, governments, workers, students, education, and training systems—currently face, and which ultimately determine the equilibrium in labor markets. Second, the report proposes a medium term roadmap of policy options that could promote the robust and inclusive growth needed to tackle the structural employment challenge for the region. Third, the report aims to inform and open up a platform for debate on jobs among a broad set of stakeholders, with the ultimate goal of contributing to reach a shared view of the employment challenges and the reform path ahead.